THE CIRCLE OF SUBGENRES AS A POSSIBLE WAY TO DESCRIBE THE INNER STRUCTURING OF FANTASY LITERATURE - Zelinová, Tereza (Bohemica Olomucensia, 2021)
This paper introduces the theory of the circle of subgenres of fantasy literature. This theory combines the standard (fan) inner division of fantasy into high, heroic, urban etc. and selected scientific theories dealing with fantasy literature. The need to create a circle of subgenres is based on the extent of the fantasy genre and its growing popularity, as well as inconsistencies in the definition of subgenres, especially by fans' definitions. The circle of subgenres can be applied to the so-called core texts, which can be found using Attebery's theory of fuzzy sets, Wittgenstein's theory of of family resemblance and particular intertextual characteristics. These core texts are then divided into individual subgenres according to their distinctive features. The paper draws attention to certain differences between the understanding of subgenres in the Czech and Anglo-Saxon environment, which exist due to the unique development of fantasy in the Czech cultural environment.
Keywords: czech fantasy literature; core texts; the circle of subgenres; definition of fantasy literature; fuzzy sets